Increasing energy awareness through effective advertising messages – a neurophysiological approach to engagement study - Piwowarski, Bartłomiej (Human Technology, 2024)
The article presents the application of neurophysiological measurements to evaluate the effectiveness of advertising messages to increase energy awareness. The study focuses on two commercials promoting pro-ecological behaviors. The level of audience engagement was analyzed using the engagement index (EI), which was determined based on EEG studies. The results showed that appropriately designed scenes (surprising, humorous situations, longer rather than shorter ones, etc.) could increase engagement. Maintaining the upward trend in engagement, confirmed by the time analysis of EI, validated the alignment of the advertisement design with models of advertising impact on the audience. The study demonstrated that EEG is an effective tool for assessing audience reactions to advertisements, which can lead to more effective advertising campaigns promoting pro-ecological behaviors.